The structure of bank relationships, endogenous monitoring, and loan rates - Carletti, Elena (Journal of Financial Intermediation, 2004)
This paper investigates a firm's choice between borrowing from a single bank and from two banks. The focus is on how this decision affects banks' equilibrium monitoring intensities and loan rates. Two-bank lending suffers from duplication of effort and sharing of monitoring benefits, but it benefits from diseconomies of scale in monitoring. Thus, two-bank lending involves lower monitoring but not necessarily higher loan rates than single-bank lending. The optimal borrowing structure balances the benefit of monitoring for the firm in terms of higher success probability of the project against its drawbacks of lower expected private return and higher total monitoring costs. In contrast to the previous theoretical literature, the model lays down an explanation for the empirical observation that multiple-bank lending does not unambiguously increase loan rates or firms' quality, in particular in small business lending.